Classical Heroes in the 21st Century New Perspectives on Contemporary Cinematic Narratives of Antiquity - Lindner, Martin; Steffensen, Nils (Helden - Heroisierungen - Heroismen, 2023)
The study of ancient heroes in film provides an eminent contribution to our understanding of the present by identifying the upheavals, conflicts, crises and resolution strategies that manifest themselves in heroic figures. This volume approaches heroizations by examining political leadership in heroic narratives and the influence of ancient heroes on the construction of modern (super-)heroes. Studies on the negations of the heroic reveal ambivalence, fluidity and legitimization difficulties of the examined figures. Contributions on narrativization and aesthetics address didactic potentials, genre influences, intermedial references and the possible future of (de)heroization in cinematic antiquity. With contributions by Anastasia Bakogianni | Torsten Caeners | Georg Eckert | Luis Unceta Gómez | Wolfgang Hochbruck | Silvester Kreisel | Martin Lindner | Krešimir Matijević | Nils Steffensen | Alexander Vandewalle | Martin M. Winkler